2019
DOI: 10.1111/jfd.12984
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characterization of Edwardsiella isolates from different fish species and geographical areas in Asia: Implications for vaccine development

Abstract: The genus Edwardsiella is one of the major causes of fish diseases globally. Herein, we examined 37 isolates from ten different fish species from India, South Korea and Taiwan to gain insight into their phenotypic and genotypic properties, of which 30 were characterized as E. tarda with phenotypic homology estimated at 85.71% based on API‐20E biochemical tests. Genotyping using 16S rRNA put all isolates together with E. anguillarum, E. hoshinae, E. tarda, E. piscicida and E. ictaluri reference strains in a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…in China (Shao et al, ). Since then, several isolates once identified as E. tarda or E. piscicida have been reassigned to E. anguillarum (Buján et al, ; Dubey et al, ; Shao et al, ). Its presence in the United States has been demonstrated among archived isolates from striped bass ( Morone saxatilis ) dating back to 1994 (Reichley et al, ).…”
Section: Antimicrobial Minimum Inhibitory Concentrations (Mics) Againmentioning
confidence: 99%
See 1 more Smart Citation
“…in China (Shao et al, ). Since then, several isolates once identified as E. tarda or E. piscicida have been reassigned to E. anguillarum (Buján et al, ; Dubey et al, ; Shao et al, ). Its presence in the United States has been demonstrated among archived isolates from striped bass ( Morone saxatilis ) dating back to 1994 (Reichley et al, ).…”
Section: Antimicrobial Minimum Inhibitory Concentrations (Mics) Againmentioning
confidence: 99%
“…In conjunction with E. piscicida , E. anguillarum is emerging as a fish pathogen with an expanding host range (Buján et al, ; Dubey et al, ; Griffin et al, ). Information concerning impacts of E. anguillarum infection and its associated histopathologic changes is limited, although several investigations indicate variation in pathogenicity among isolates, as well as differences in virulence among diverse fish species (Abayneh et al, ; Reichley, Ware, Greenway, Wise, & Griffin, ; Reichley et al, ).…”
Section: Antimicrobial Minimum Inhibitory Concentrations (Mics) Againmentioning
confidence: 99%
“…It also causes fish gangrene, emphysematous putrefactive disease, red disease, and enteric septicemia in carp, catfish, and several other fish species (32,33). (11,20,21) However, in a recent study, we showed that piscine Edwardsiella isolates from 10 fish species in India belonged to Edwardsiella piscicida and Edwardsiella anguillarum (34). Therefore, it is likely that all fish isolates previously classified as E. tarda were either E. piscicida or E. anguillarum.…”
Section: Major Bacterial Fish Pathogens In Indiamentioning
confidence: 95%
“…Together with recombinant DNA technology, WGS has contributed to improving OMP vaccine design, while protein sequence comparison has proved to be a powerful tool used to identify immunogenic proteins that are broadly protective against variant pathogen strains. For example, Dubey et al (34) used protein sequence comparison and phylogenetic analysis to show that the OmpW of E. piscicida and E. anguillarum had high similarity, suggesting that a common antigen can be used against isolates from different fish species and geographical areas in Asia.…”
Section: Development Of Vaccine Candidates Through Epitope Mappingmentioning
confidence: 99%
“…Sequences were used to generate 16S rRNA and gyrB phylogenetic trees in MEGA7 bioinformatics software [ 6 ]. The evolutionary history for each tree was inferred using the Maximum Composite Likelihood method [ 7 ] as described in our previous study [ 8 ]. Genetic distances were computed using Kimura’s two-parameter value [ 7 ].…”
Section: Main Textmentioning
confidence: 99%